DEGENERATIONS OF COMPLEX DYNAMICAL SYSTEMS - LAURA DE MARCO; XANDER FABER (Forum of Mathematics, Sigma, 2014)
We show that the weak limit of the maximal measures for any degenerating sequence of rational maps on the Riemann sphere